PENGARUH SUMBERDAYA MANUSIA, KINERJA DAN BUDAYA KERJA TERHADAP PELAYANAN PUBLIK DI KANTOR DINAS ENERGI DAN SUMBERDAYA MINERAL DAERAH PROVINSI SULAWESI UTARA - LUKAS, YOAS ELLYASAF; KEKENUSA, JHON; PIOH, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
As the executor of development and state administrators, the government in this case employees (ASN andTHL) is obliged to protect (to protect the people), serve (to serve the people), and regulate (to regulate thepeople) all of which are "service delivery or public service ", in the context of fulfilling public interests(public interest) and addressing public affairs. The government needs to understand with certainty what itsthe role is in public service, how to realize service quality (Servqual) that satisfies the people as recipients ofservices, and how attitudes should behave as the government (Surjadi, 2009).According to Sinambela (2010), every human being needs service, even in the extreme it can be said thatservice cannot be separated from human life. Therefore, the services / public services provided to the publicrequire certain qualities. The service provided by the management through its apparatus, even though it isnot aimed at seeking profit, must still prioritize the quality of service in accordance with the demands,expectations, and needs of the people served. In an increasingly critical community condition, publicbureaucracy is demanded to be able to change its position and role (revitalization) in providing publicservices. From those who like to rule and rule to being like serving. From those who like to use the powerapproach, it turns to be helpful to be flexible, collaborative, and dialogic. From slogan ways to pragmatic realistic ways of working.Keyword: Human Resources, Performance, Work Culture, Public Services